‘Heaven guide him to thy husband’s cudgel’: Falstaff as Male Witch in The Merry Wives of Windsor - Vogel Kubik, Sharon (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
This essay argues that in Shakespeare’s The Merry Wives of Windsor, when the merry wives dress Falstaff as the old woman of Brentford, they reveal his true character by visually associating him with a witch and thus force the men of Windsor to punish him for his crimes. Falstaff’s behaviour matches the social disruption of the male witch; furthermore, his position as a new and unestablished member of a community, his gender, and the fact that the authorities of Windsor are inept make it difficult for the merry wives to successfully accuse him without appealing to popular witchcraft belief.